A meta-analysis of the relationship between anxiety and telomere length. Issue 3 (4th May 2017) - Malouff, John M.; Schutte, Nicola S.
ABSTRACT: Background and objectives: Telomeres are protective caps at the ends of chromosomes, and shorter telomeres are associated with poor physical health. The present study set out to consolidate the varying effect sizes found so far in studies of anxiety and telomere length. Design and methods: A meta-analytic investigation of the relationship between anxiety and telomere length used information from 17 different samples comprising a total of 19, 424 participants. Results: The results showed a small but significant association, r = −.06, between higher anxiety and shorter telomeres. Studies comparing individuals diagnosed with an anxiety disorder with other individuals had a significant effect size, and studies that did not use this comparison threshold did not have a significant effect size. Conclusions: Anxiety is associated with an important biomarker related to health. Future experimental studies that examine the impact of interventions intended to reduce anxiety in conjunction with measurement of telomere length can further clarify the impact of anxiety on telomere length.